Profile of Unnatural Deaths in Females A Retrospective Study - Pawar, CK; Bhullar, DS; Oberoi, SS; Aggarwal , KK (Journal of Indian Academy of Forensic Medicine, 2014)
Right from the time of conception in her mother’s womb, till her death, a woman is subjected to one or the other crime/ torture/ inhuman behavior. Crimes against women are increasing at an alarming pace in our country. The male-female ratio is also declining. This study was undertaken at the Department of Forensic Medicine, GMC Patiala, to understand the contribution of social conditions towards the main causes of unnatural female deaths. A total of 100 cases were studied. Of these, 55% cases were from rural area; 68% were in the age group of 18 to 30 years. Majority of the victims comprised married female. Forty one percent of them died within seven years of marriage; 55% victims were matriculate and 11% were illiterate. Most of the deaths, 57% were reported as accidental, while 30% were reported as suicidal and 11% were homicidal in manner. The most common precipitating factor was dowry. Maximum victims died as a result of burn injuries. In homicidal cases, 45% victims were killed by burning. Poisoning was the commonest cause of suicidal deaths, 60%. In accidental deaths, 53% victims died as a result of accidental burning.